A prospective randomized exploratory study comparing the efficacy of once‐daily topical 0.5% 5‐fluorouracil in combination with 10.0% salicylic acid (5‐FU/SA) vs. cryosurgery for the treatment of hyperkeratotic actinic keratosis. (25th September 2014) - Simon, J.‐C.; Dominicus, R.; Karl, L.; Rodríguez, R.; Willers, C.; Dirschka, T.
Abstract: Background: Actinic keratoses (AKs) are clinically significant and require therapy. Efficacy of low‐dose (0.5%) 5‐fluorouracil with 10% salicylic acid (5‐FU/SA) has been shown in randomized comparative trials of hyperkeratotic lesions of various grades. Objectives: To evaluate the efficacy, tolerability and safety of low‐dose 5‐FU/SA topical solution vs. cryosurgery in patients with moderate/severe (grade II/III) hyperkeratotic AKs (NCT01358851). Methods: In an exploratory, open, randomized study, patients with histologically confirmed moderate/severe hyperkeratotic AKs on the face/forehead or bald scalp received 6 weeks of once‐daily topical 0.5% 5‐FU/SA, or up to two cryosurgery treatments (3 weeks apart). Histological outcomes were determined from punch biopsies. Clinical, cosmetic and tolerability outcomes were also assessed. Results: Sixty‐six patients received treatment (33 per arm). The baseline total number of lesions was 266 (8.1/patient) in the 0.5% 5‐FU/SA and 263 (8.0/patient) in the cryosurgery group. Most (74.5%) lesions were grade II (grade III, 25.5%). Mean change in lesion count from baseline to Day 98 was −5.2 and −5.7 lesions per patient for 0.5% 5‐FU/SA and cryotherapy groups respectively. Histological AK clearance rates on Day 98 were 62.1% and 41.9% respectively. At 6‐month posttreatment follow‐up, recurrence of cleared lesions (no clinically visible lesions in treatment area) occurred in 39.4% of 0.5% 5‐FU/SA and 84.8% of cryosurgery patients. Drug‐related adverse events (AEs), including local skin reactions considered 'severe' by the investigator, were reported in 24.2% of 0.5% 5‐FU/SA and 6.1% of cryosurgery patients. All drug‐related AEs were skin reactions. Conclusions: Although the study was not powered to explore statistical differences in clinical efficacy between treatments, a short (6‐week) schedule of topical treatment with 0.5% 5‐FU/SA achieved greater histological clearance and lower recurrence of grade II/III hyperkeratotic AKs than cryosurgery. AE incidence across both treatment groups was relatively low and AEs were generally mild or moderate. Clinical trials.gov identifier: NCT01358851.